Human tonsil intraepithelial B cells: a marginal zone-related subpopulation. Issue 8 (August 1992) - Morente, M; Piris, M A; Orradre, J L; Rivas, C; Villuendas, R
Abstract : AIMS: To determine if intraepithelial B cells in reactive human palatine tonsils were similar to the marginal zone cells of the spleen and Peyer's patches. METHODS: Reactive human palatine tonsils were studied using conventional methods of light microscopy, electron microscopy, and a panel of monoclonal antibodies for leucocyte common antigens. RESULTS: Clinically important numbers of marginal zone-related B cells around the mantle zone were absent in lymphoid follicles, but in the cryptal epithelium there were abundant lymphoid cells with centrocyte-like nuclei and clear cytoplasm, intermingled with macrophages and plasma cells. The immunophenotype of these intraepithelial B cells was distinctive and similar to that found in the splenic marginal zone cells (IgM+, IgD-, CD23-, CD10-, CD35+, CD21+, bc12+, KB61+). CONCLUSIONS: Intraepithelial B cells in human tonsil could represent the counterpart of the marginal zone described in Peyer's patches. Their presence within the epithelium could reflect the destination for the malignant B cells in the lymphoepithelial lesion of mucosa associated lymphoid tissue (MALT) lymphomas. Human palatine tonsil lymphoid tissue has morphological, immunophenotypic, and pathological features similar to those of MALT.